2017
DOI: 10.3233/bmr-160550
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder proprioception in patients with subacromial impingement syndrome

Abstract: This study showed that shoulder proprioception was impaired in patients with SIS. This proprioceptive impairment was found not only in involved shoulders but also in uninvolved shoulders in patients with SIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
3
29
0
3
Order By: Relevance
“…To date, there is only one study that included a comprehensive assessment of shoulder proprioception (including the passive and active joint position sense and kinesthesia) in patients with SAPS. 6 The authors concluded that shoulder proprioception is impaired in patients with SAPS using a painful position to assess the proprioception acuity.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, there is only one study that included a comprehensive assessment of shoulder proprioception (including the passive and active joint position sense and kinesthesia) in patients with SAPS. 6 The authors concluded that shoulder proprioception is impaired in patients with SAPS using a painful position to assess the proprioception acuity.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SAPS or rotator cuff injury can present reduced proprioception when compared to controls. Thus, proprioceptive training is commonly used in clinical practice for the treatment of the shoulder injuries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations